KONSEP KOMUNIKASI KEPEMIMPINAN DAKWAH DALAM MENGHADAPI GENERASI DIGITAL - Dwi Budiman Assiroji (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2021)
Research Objectives: This study aims to find out how the concept of da'wah communication should be carried out by a da'wah leader in facing the digital generation. Research Methodology: Qualitative-Literature. Research Results: from this study it was found that in facing the digital generation, a da'wah leader must pay attention to at least three things in communicating. Namely: first, you must be an example in your life, especially in the context of da'wah. Because the digital generation is a generation that really pays attention to the lives of its characters. Second, da'wah leaders must make maximum use of online media as a medium for preaching to the digital generation. Because the digital generation is a generation that is very familiar with online media. Third, the da'wah leader must have digital literacy in communicating with the digital generation. The three literacies are data literacy, technological literacy and human literacy. So that with this literacy, da'wah leaders can communicate well with the digital generation.